HISTORY EDUCATION IN BORDERLINE TERRITORY - Ardhana, I ketut (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
Indonesian government policies that emphasize economic growth and national stability, characterized by authoritarian and centralized government in the past, inflict a disparity in regional growth. The control of central government to the region, seems to disturb the sense of justice and the welfare of the people on the borderline territory which are considered retarded, isolated, and marginalized. Moreover, the increasing of smuggling, human trafficking, and terrorism has been disturbing the sense of historical awareness in relation to the issue of nationality. It started from reform era followed by regional autonomy policy gives space to the region government to balance the local development. This article discussed, first: The importance of History education in borderline territory, Second: ethnic historical concept and regional studies in borderline territory, third: ethnical integration based on sociocultural aspect of national character reinforcement in borderline, and fourth: history education development to increase the competitiveness, which also expected to strengthen the nationalism in borderline territory.